KEMAMPUAN ALKALINITAS KAPASITAS PENYANGGAN (BUFFER CAPACITY) DALAM SISTEM ANAEROBIK FIXED BED - Djoko Padmono (Jurnal Teknologi Lingkungan, 2007)
In the process of decomposition of the organic matter with the anaerobicsystem was learnt that the methane forming bacteria of was verysensitive to the level of the acidity in other words very sensitive with thelow pH. There are by two big groups the bacteria that was active in thissystem. These two bacteria group had the duplication capacity thatwas very different that is 3 hours during the acid forming bacteria of and3 days for the methane forming bacteria. The alkalinity in the reactorwith the certain concentration between 1000 – 5000 mg/l could supportthe pH continue to in the neutral condition when the decline in the pHhappened so as the balance of the process could on the whole stayproceeding normally.It was observed that achieving the pH 3 in the feeding, the concentrationof the alkalinity descended through to 500 mg/l this was the loweredcondition and the process of decomposition of the organic matter wasdisrupted. When being left alone then the system will stop completelybecause of the methane forming bacteria was inhibited.